Assessment of quality of routine immunization in rural areas of Doiwala Block, Dehradun - Prakash Kumar; Rohit Katre; Pallavi Singh; Mahendra Singh; Vartika Saxena (Journal of Family Medicine and Primary Care, 2023)
Background: India initiated Expanded Programme on Immunization (EPI) in 1978 and was renamed to Universal Immunization Programme (UIP) in 1985 and subsequently integrated with National Rural Health Mission (NRHM) in 2005. Many studies have shown that health workers involved in immunization are more concerned towards coverage than the quality of immunization services provided. Aims and Objectives: This study aimed to assess the quality of routine immunization services in rural areas of Doiwala Block of Dehradun, Uttarakhand. Material and Methods: It was a cross-sectional study conducted for a duration of one year. Study participants included Auxillary Nurse Midwives (ANMs), Accredited Social Health Activists (ASHAs), Anganwadi Workers (AWWs) and parents/caregivers of children aged 12–23 months residing in that area who had received immunization services on the day of the survey. Institutional ethics committee clearance was obtained before the start of the study. A P value of <0.05 was considered as statistically significant. Results: ASHAs at two centres in low-performing centres had never undergone any training for routine immunization but there was no statistically significant difference found between high and low-performing centres (P > 0.05). The most common vaccine not available was the Bacillus Calmette–Guérin (BCG) vaccine. The majority of clients at both high (92%) and low-performing centres (96%) said that they never waited for at least 30 min post-vaccination at the vaccination site for observation. Conclusion: The study highlights that most of the ANMs at the immunization centre were having good knowledge and were adequately trained for maintaining cold chains at session sites.